Comparison of nominal and real rigidities: Fiscal policy perspective - Piotr Krajewski (Comparative Economic Research. Central and Eastern Europe, 2014)
This paper examines the impact of nominal and real rigidities in the economy on the effects of fiscal policy. The study confirmed the hypothesis that both nominal and real rigidities enhance the impact of fiscal policy on the Polish economy. In the case of nominal price rigidity it was found that the impact of government spending on GDP depends on the conduct of monetary policy. On the other hand, under conditions of wage rigidity, the strength of fiscal multipliers depends on the slope of the labour supply curve. The study also examined two types of real rigidities - lack of access to the credit market, and consumer habits. Analyses show that the above rigidities result primarily in a strong positive relationship between government spending and the level of consumption
Keywords: 330; fiscal policy; nominal rigidities; real rigidities